Comprehensive flow cytometric reference intervals of leukocyte subsets from six study centers across Europe - Oras, Astrid; Quirant‐Sanchez, B.; Popadic, D.; Thunberg, S.; Winqvist, O.; Heck, S.; Cwikowski, M.; Riemann, Dagmar; Seliger, Barbara; Martinez Caceres, E.; Uibo, R.; Giese, Thomas (Clinical & experimental immunology, 2020)
blood leukocyte counts, flow cytometry, immunophenotyping, reference intervals
Published: 03 August 2020
Gesehen am 20.12.2021